Contribution of women to household labour input into the subsistence goat husbandry in eastern Ethiopia - Ayalew, W.; Rischkowsky, Barbara A.; King, J.M.; Bruns, E.W.; Kassa, B.; Peacock, C.P. (Institut National de la Recherche Agronomique, 2000)
Individual labour input into goat husbandry was enumerated for a period of one year from a total of 71 sample households. Comparison was made at household level. Results show that women contribute a proportional share of labour and their share changes in response to household characteristics related to resource use. But the changes are not similar to those of average household labour input. The involvement of other members of the household cannot therefore be neglected in goat Development interventions. Implementation of a womenfocused project has increased not only the amount of labour that women contribute, but also their share of the total household input. A strong negative correlation was observed between per capita holding of cultivated land and labour input to goat husbandry.